Softskill Development of Educational Staff in Providing Service for Student at UPN “Veteran” Jatim - S. Hardjati; A. Prathama; R. Febrianita (Future Science)
The development of human resources in an organization begins with the development of employee soft skill not to put aside the hard skills itself. Longsighted the growth of universities in Indonesia; it is necessary to strengthen the soft skill of human resources both in state and private universities. Universitas Pembangunan Nasional (UPN)